Urban Transportation and Rising CO Emissions: A Case Study of East Jakarta and its Public Health Impacts - Ernyasih Ernyasih; Anwar Mallongi; Munaya Fauziah; Gilang Anugerah Munggaran; Firda Ayu Salsabilla; Wesam AL Madhoun; Fini Fajrini; Taufiqurrochman Taufiqurrochman (Journal of Public Health and Pharmacy, 2025)
Introduction: Carbon monoxide (CO) emissions from urban transportation present a critical challenge for air quality, public health, and environmental sustainability. East Jakarta, with its rapid motorization and chronic traffic congestion, serves as a case study for the broader impacts of urban CO pollution. This study investigates the correlation between CO levels and traffic density, providing empirical insights into the dynamics of transportation-driven air pollution in densely populated cities. Methods: A quantitative cross-sectional study was conducted in July 2024, measuring CO concentrations at 15 strategic locations using calibrated CO meters. Sampling sites were selected based on traffic volume, population exposure, and historical emission data to ensure a comprehensive urban representation. Data analysis included descriptive statistics, normality tests, and regression analysis to evaluate relationships between CO levels, traffic patterns, and supporting variables. Results: Findings revealed an average CO concentration of 6,665 µg/m³, with Jatinegara Kaum (15,380 µg/m³) and Duren Sawit (13,031 µg/m³) exceeding the government air quality threshold (10,000 µg/m³). A strong positive correlation (R² = 0.78, p < 0.05) was identified between traffic congestion and CO levels, confirming vehicular emissions as the dominant contributor. Moreover, no significant correlation with weather variables was observed, further emphasizing the role of transportation in shaping local air quality. Conclusion: These results underscore the urgent need for policy interventions, including the expansion of electric vehicle infrastructure, congestion pricing, and green urban planning. This study also highlights the necessity of integrating real-time air quality monitoring and AI-based traffic flow management to optimize pollution control efforts. By situating East Jakarta’s case within global urban air pollution trends, these findings offer scalable insights applicable to other rapidly urbanizing cities worldwide.